2005
DOI: 10.1530/rep.1.00699
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrites and impaired modulation of nitric oxide concentrations in embryos from diabetic rats during early organogenesis

Abstract: Maternal diabetes significantly increases the risk of congenital malformation, a syndrome known as diabetic embryopathy. Nitric oxide (NO), implicated in embryogenesis, has been found elevated in embryos from diabetic rats during organogenesis. The developmental signaling molecules endothelin-1 (ET-1) and 15-deoxy D 12,14 prostaglandin J 2 (15dPGJ 2 ) downregulate embryonic NO levels. In the presence of NO and superoxide, formation of the potent oxidant peroxynitrite may occur. Therefore, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 52 publications
4
29
0
Order By: Relevance
“…In Alx3 -deficient embryonic cells, excess oxidative stress is a consequence of increased production of ROS, as well as of reactive nitrogen species evidenced by elevated nitrotyrosine content and expression of inducible NOS, which has been implicated in the pathogenesis of embryonic malformations induced by maternal diabetes 43, 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In Alx3 -deficient embryonic cells, excess oxidative stress is a consequence of increased production of ROS, as well as of reactive nitrogen species evidenced by elevated nitrotyrosine content and expression of inducible NOS, which has been implicated in the pathogenesis of embryonic malformations induced by maternal diabetes 43, 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Although nitric oxide is a weak free radical, its oxidant properties are enhanced when nitric oxide reacts with a superoxide to form peroxynitrite [22]. Jawerbaum et al reported that intense nitrotyrosine immunostaining indicative of peroxynitrite was detected in the neural tube and neural folds of embryos of diabetic rats [23]. These findings suggest that increased expression of iNOS in diabetic embryos results in an excess of nitric oxide, which then leads to peroxynitrite accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide reacts with superoxide to form the powerful oxidant, peroxynitrite (ONOO − ), which is thought to play a role in nitric oxidedependent cytotoxicity [22]. It has been reported that NOS activity and nitric oxide levels are elevated and that peroxynitrite is formed in the maldeveloped neural tube of embryos of diabetic dams [23]. Based on these findings, we hypothesised that maternal hyperglycaemia might induce iNOS expression in the neural tube of embryos and that the overproduction of nitric oxide is involved in diabetic embryopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NO may directly interact with ROS generated under hyperglycemic conditions to form potent oxidant peroxynitrite leading to nitrosative stress 40, 41 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%